ACG Clinical Guideline: Diagnosis and Management of Adenomatous Colorectal Polyposis Syndromes - Gautam Mankaney; Gregory E. Idos; Elena M. Stoffel; Jennifer M. Weiss; Shailja Shah; Emad Qayed; Mary Pat Harnegie; Carol A. Burke (American Journal of Gastroenterology, 2026)
The hereditary adenomatous colorectal polyposis syndromes are incurable, systemic, cancer risk predisposition syndromes with substantial morbidity and mortality. They differ in their mode of inheritance, age at disease onset, phenotypic expression, and cancer risk. The most common cancer risks involve the gastrointestinal tract including the colon, rectum, duodenum, ampulla, and stomach. Identifying these syndromes through personal and family history risk assessment and germline genetic testing, along with timely surgical and endoscopic management, can reduce cancer incidence and mortality. These guidelines use the Grading of Recommendations, Assessment, Development, and Evaluation methodology to provide clinical guidance on the selection of individuals who should undergo a risk assessment for a hereditary adenomatous colorectal polyposis syndrome, modality and timing of germline genetic testing, cancer risk mitigation through endoscopic and surgical interventions, and the role of chemoprevention. This document reviews the approach to genetic testing in patients with phenotypic colorectal polyposis and the impact of presymptomatic diagnosis in families with a known familial germline pathogenic variant or clinical features suggestive of a hereditary adenomatous polyposis syndrome. Management strategies for patients based on genetic test results or without genetic testing are provided. We also review colorectal and extracolonic phenotypic benign and malignant manifestations of the known hereditary syndromes with a focus on the 2 most common hereditary colorectal polyposis syndromes: familial adenomatous polyposis and MUTYH -associated polyposis. The document concludes with recommendations on polyposis and cancer risk mitigation strategies and highlights updates to management since the previous guideline was published.